2016
DOI: 10.1007/s00299-016-2062-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient targeted multiallelic mutagenesis in tetraploid potato (Solanum tuberosum) by transient CRISPR-Cas9 expression in protoplasts

Abstract: Key message Altered starch quality with full knockout of GBSS gene function in potato was achieved using CRISPR-Cas9 technology, through transient transfection and regeneration from isolated protoplasts. AbstractSite-directed mutagenesis (SDM) has shown great progress in introducing precisely targeted mutations. Engineered CRISPR-Cas9 has received increased focus compared to other SDM techniques, since the method is easily adapted to different targets. Here, we demonstrate that transient application of CRISPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
297
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(321 citation statements)
references
References 42 publications
15
297
1
8
Order By: Relevance
“…CRISPR/Casнаправленный нокаут генов также пер спективен для улучшения признаков качества и техниче ских характеристик сырья. Например, у картофеля нокаут гена GBSS, кодирующего фермент биосинтеза крахмала, гранулсвязанную крахмалсинтазу, приводит к измене нию свойств крахмала за счет сдвига в нем соотношения количества линейных (амилоза) и разветвленных (амило пектин) полисахаридов в пользу последних (Andersson et al, 2017). Крахмал с высоким содержанием амилопектина дает гели повышенной оптической прозрачности, устой чивости при центрифугировании, а также демонстриру ет повышение максимальной и конечной температуры желатинизации и измененные реологические свойства (Хлесткин и др., 2017).…”
Section: Plant Genetics Vavilov Journal Of Genetics and Breeding • 21unclassified
“…CRISPR/Casнаправленный нокаут генов также пер спективен для улучшения признаков качества и техниче ских характеристик сырья. Например, у картофеля нокаут гена GBSS, кодирующего фермент биосинтеза крахмала, гранулсвязанную крахмалсинтазу, приводит к измене нию свойств крахмала за счет сдвига в нем соотношения количества линейных (амилоза) и разветвленных (амило пектин) полисахаридов в пользу последних (Andersson et al, 2017). Крахмал с высоким содержанием амилопектина дает гели повышенной оптической прозрачности, устой чивости при центрифугировании, а также демонстриру ет повышение максимальной и конечной температуры желатинизации и измененные реологические свойства (Хлесткин и др., 2017).…”
Section: Plant Genetics Vavilov Journal Of Genetics and Breeding • 21unclassified
“…As specific primers are used to detect the presence of transgenes encoding CRISPR/Cas components, scientists showed that transgene-free, T2 mutant lines could be obtained by genetic segregation: the targeted mutations were stably passed on in transgene-free plants [ Table 1, column 'Transgene-free plants studied (Yes/No)']. Other studies show how to generate transgene-free plants using alternative delivery methods [11,12]. These methods include ways of introducing the CRISPR components in a transient fashion such that integration is unlikely, for example using protoplast systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show how to generate transgene-free plants using alternative delivery methods [11,12]. These methods include ways of introducing the CRISPR components in a transient fashion such that integration is unlikely, for example using protoplast systems [12]. Alternatively, it is possible to avoid the presence of foreign DNA at any stage of the process, therefore avoiding the possibility of foreign DNA insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Mariette Anderson has worked with an industrial partner, Lyckeby, to develop a potato variety that has reduced levels of amylose. This was achieved by successfully editing four copies of the GBSS gene (Box B; Anderson et al 2017). Attila Molnars' group used CRISPR-Cas9 to introduce a single base deletion into the Arabidopsis eLF(iso)4E gene, which subsequently confers viral resistance (Box C; Pyott et al 2016).…”
Section: Box a Laurence Tomlinson The Sainsbury Laboratory Norwichmentioning
confidence: 99%